Video Method Education and Demonstration of First Aid Capabilities for Dehydration in Children with Diarrhea: Study of Mothers in Siding Village, Tuban - Didit Damayanti; Pria Wahyu Romadhon G (International Journal of Health and Medicine, 2025)
Dehydration occurs when the body loses too much water and essential fluids in the body. Diarrhea is the main cause of dehydration in toddlers. Toddlers often get diarrhea because their immune system is still vulnerable. If the problem of dehydration is not addressed immediately, it can lead to other health problems such as shock risk. This study aims to determine the effect of video education and demonstration on the ability of first aid dehydration due to diarrhea in mothers with children 0-5 years in Siding Tuban Village. The research design used was Pre Experimental with a one group pretest-postest approach, a sample of 16 respondents taken from 66 populations through Purposive Sampling. Research instrument Ability was measured by observation sheet and analyzed using Wilcoxon Signed Rank test (α=0.05). Before the intervention, 93.8% of respondents had poor skills and after the intervention, 100% of respondents had good skills, which showed an increase in the value of dehydration first aid skills. The results of the analysis obtained p-value=0.000 (<α), meaning that there is an effect of education on the ability of first aid for dehydration due to diarrhea in children. The combination of video and demonstration methods improves the mother's ability to dehydrate children due to diarrhea through visualization and hands-on practice, facilitating understanding and effective application. It is expected that mothers can carry out first aid for dehydration due to diarrhea in children without guidance, reducing the risk of child mortality.